The Influence of Social Media on Insight Nationality in the Younger Generation - Dinda Adellia (International Journal of Students Education, 2024)
This literature study aims to investigate the influence of social media on national insight in the younger generation by targeting relevant research. The literature review method is used to explore several views and findings that have been expressed in the scientific literature regarding this topic. By taking into account the various perspectives and research methodologies used in the selected studies, this analysis allows for a cooperative explanation of the relationship between social media and national insight in the younger generation. The results of the literature review show that the use of social media by the younger generation has a significant influence on the formation of national identity and understanding of national issues. Although there is research that highlights the positive impact of social media in increasing awareness of national identity and increasing feelings of social solidarity, there is also much research that highlights the potential of social media to strengthen polarization, spread inaccurate information, and trigger conflict between groups. Additionally, factors such as the type of content consumed, intensity of use, and individual characteristics may moderate the relationship between social media and national insight. These findings underscore the complexity of the dynamics between social media and national identity in the younger generation. The implications of this literature study highlight the importance of a deep understanding of the role of media in shaping the national outlook of the younger generation, as well as the need for a holistic approach in overcoming the challenges and opportunities associated with the use of social media in nationalism. Further research exploring the interactions between social media, national identity, and relevant moderating media factors is expected to provide deeper insights for developing more effective educational policies and practices.